Targeting Mitochondrial Dysfunction and Oxidative Stress to Prevent the Neurodegeneration of Retinal Ganglion Cells - Elisabetta Catalani; Kashi Brunetti; Simona Del Quondam; Davide Cervia (Antioxidants, 2023)
The imbalance of redox homeostasis contributes to neurodegeneration, including that related to the visual system. Mitochondria, essential in providing energy and responsible for several cell functions, are a significant source of reactive oxygen and/or nitrogen species, and they are, in turn, sensitive to free radical imbalance. Dysfunctional mitochondria are implicated in the development and progression of retinal pathologies and are directly involved in retinal neuronal degeneration. Retinal ganglion cells (RGCs) are higher energy consumers susceptible to mitochondrial dysfunctions that ultimately cause RGC loss. Proper redox balance and mitochondrial homeostasis are essential for maintaining healthy retinal conditions and inducing neuroprotection. In this respect, the antioxidant treatment approach is effective against neuronal oxidative damage and represents a challenge for retinal diseases. Here, we highlighted the latest findings about mitochondrial dysfunction in retinal pathologies linked to RGC degeneration and discussed redox-related strategies with potential neuroprotective properties.